Evaluation Of The Prevalence Of Postpartum Depression In Women In Punjab's Patiala District Through Structural Equation Modeling - Kaur, Rupinder; Kaushal, Shaveta; Sood, Darpan (Journal of Neonatal Surgery, 2025)
Postpartum Depression (PPD) is a significant health obstacle for maternal care due to the wide reaching consequences on mothers and their children. In order to investigate the prevalence of PPD and associated risk variables, PLS-SEM (Partial Least Squares Structural Equation Modeling) was utilized by analysed women’s data in District Patiala, Punjab. The findings indicated that among 400 new mothers, socioeconomic status and social network support are the primary risk factors for postpartum depression (PPD), while prior mental health conditions and pregnancy issues are secondary risk factors. The study found that the strongest predictors of PPD were having little family support and having a difficult financial situation. Furthermore, these PLS-SEM results show how the factors interact in a complex way, supporting each other through policy measures aimed to the improvement of mental health treatment and community development